2017
DOI: 10.1073/pnas.1619657114
|View full text |Cite
|
Sign up to set email alerts
|

Temporal binding function of dorsal CA1 is critical for declarative memory formation

Abstract: Temporal binding, the process that enables association between discontiguous stimuli in memory, and relational organization, a process that enables the flexibility of declarative memories, are both hippocampus-dependent and decline in aging. However, how these two processes are related in supporting declarative memory formation and how they are compromised in age-related memory loss remain hypothetical. We here identify a causal link between these two features of declarative memory: Temporal binding is a neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
45
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 32 publications
10
45
4
Order By: Relevance
“…Here we have implemented a novel experimental framework for deciphering neural coding during non-spatial, temporal associative learning in the hippocampus using chronic cellular imaging. These methods demonstrate that network dynamics during trace fear conditioning are inconsistent with hypotheses of persistent sequential [Kitamura et al, 2015, Sellami et al, 2017] or sustained [Kaminski et al, 2017] activity in CA1. Rather we find that behavioral learning in CA1 is underpinned by the emergence of a subset of cue-selective neurons with stochastic temporal dynamics across trials.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Here we have implemented a novel experimental framework for deciphering neural coding during non-spatial, temporal associative learning in the hippocampus using chronic cellular imaging. These methods demonstrate that network dynamics during trace fear conditioning are inconsistent with hypotheses of persistent sequential [Kitamura et al, 2015, Sellami et al, 2017] or sustained [Kaminski et al, 2017] activity in CA1. Rather we find that behavioral learning in CA1 is underpinned by the emergence of a subset of cue-selective neurons with stochastic temporal dynamics across trials.…”
Section: Discussionmentioning
confidence: 83%
“…We first asked whether the hippocampus generated a consistent temporal code during each trial to connect the CS and US representations [Sellami et al, 2017, Kitamura et al, 2015]. While ordering population activity by the latency of neurons’ peak firing rates naturally lends the appearance of a sequence that spans the trial period (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies that have investigated duration memory using short-term working memory tasks (13)(14)(15)(16) have often observed HPC involvement in relatively long (i.e., greater than ∼90 s) but not shorter durations, which runs counter to the proposed characteristics of time cells and the fact that studies (5)(6)(7) have observed momentto-moment time cell firing during delay periods that are less than 20 s in duration. Notably, because the HPC is suggested to be critical for sequence processing and the temporal binding of temporally discrete events (17)(18)(19)(20)(21), the involvement of this structure in representing temporal durations may be contingent on such information being embedded within a set of contiguous sequence events. Suggestive of this, we recently demonstrated using functional magnetic resonance imaging (fMRI) that human HPC activity is sensitive to changes in the durations of short intervals within event sequences (22,23).…”
mentioning
confidence: 99%